(untitled) (Orfeu, 2023)
The learning process requires engagement of the subjects in the different situations in which they are inserted. The singularities and subjectivities intertwined in these paths show the particularities and complexities that the learning process requires. When we teach how to perform a musical instrument, we cannot forget the demand that this activity requires, especially for students, namely, the development of various cognitive, metacognitive, motivational and behavioral skills. The theory of self-regulation from the socio-cognitive paradigm has been a contribution to the educational field, especially in the understanding and more assertive conduction of musical learning processes. Focusing on the self-regulatory sub-processes, this article proposes to bring some discussions from a doctoral study that had as main objective to investigate how students engaged in children’s orchestras self-regulate their musical practices and their involvement in the learning of musical memorization.